Keterlibatan Event Stakeholders pada Keberhasilan Event Pr - Lidya Wati Evelina (Bina Nusantara University, 2013)
The objective of this article is to determine how event organizers collaborate with stakeholders including the media, particular community, sponsors, participants, venue providers, accommodation providers, carteres, legal and finance personnel, production, local trade, transportation providers, government and associations for implementation Public Relations event. This paper discusses about the things that must be done for the cooperation and the benefits of cooperation undertaken. The method used in this paper is qualitative research method based on observations, literature and case studies. The results of this research note that the event organizers or companies can together with the stakeholders (the other party) make an event as mutually beneficial Public Relations. This means that all parties can achieve through the event. At the conclusion of an event Public Relations, all stakeholders involved for their own purposes. Event organizer must ensure that all stakeholders work together effectively in accordance with the agreed schedule and budget. One important feature of the agreement is to maintain a good flow of communication according to the needs of its stakeholders. All information is documented to avoid misunderstandings. Collaboration between stakeholders continuously until the event is completed. Discussion of issues that arise during the event takes place between the committee with various stakeholders is an important thing for the evaluation and response to the events that occurred.